2020
DOI: 10.1177/1747954120918964
|View full text |Cite
|
Sign up to set email alerts
|

Equipment modification can enhance skill learning in young field hockey players

Abstract: The aim of the study was to investigate whether performance of children can be improved by training with modified equipment that challenges movement execution. For that purpose, young field hockey players practiced with a modified and a regular hockey ball. The modified hockey ball enforces more variable movement execution during practice by rolling less predictably than a regular hockey ball and, thus, challenges the players’ stick–ball control. Two groups of 7- to 9-year old children, with 0 to 4 years of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…In other words, modifying equipment is considered a form of task constraint manipulation that challenges the performer to adapt to the new arrangement of constraints, resulting in a larger, degenerate movement repertoire (e.g., Davids et al, 2012 ; Ranganathan and Newell, 2013 ). For instance, Brocken et al (2020) found that practicing with a modified hockey ball that rolls less predictably than regular balls, which presumably increases movement execution redundancy and adaptivity, resulted in larger improvements in field hockey motor skills (based on a similar test as in the current study) than practicing with a regular ball. A second explanation is that equipment modification ensures better scaling of the equipment to the performer’s action capability.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…In other words, modifying equipment is considered a form of task constraint manipulation that challenges the performer to adapt to the new arrangement of constraints, resulting in a larger, degenerate movement repertoire (e.g., Davids et al, 2012 ; Ranganathan and Newell, 2013 ). For instance, Brocken et al (2020) found that practicing with a modified hockey ball that rolls less predictably than regular balls, which presumably increases movement execution redundancy and adaptivity, resulted in larger improvements in field hockey motor skills (based on a similar test as in the current study) than practicing with a regular ball. A second explanation is that equipment modification ensures better scaling of the equipment to the performer’s action capability.…”
Section: Discussionsupporting
confidence: 44%
“…Studies about modified equipment show that changing the equipment can have a positive effect on performance and learning (e.g., Farrow and Reid, 2010 ; Buszard et al, 2014 ; Timmerman et al, 2015 ; Limpens et al, 2018 ; Oppici et al, 2018 ; Brocken et al, 2020 ; Nor Azmi et al, 2020 ). At the moment, two explanations dominate in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Constraintsbased learning (CBL) is also thought to promote implicit learning processes by way of a reduction in the accrual of explicit skill knowledge. 25 According to this framework, coordinated movements emerge as a function of learners adapting to the constraints imposed on them during practice. These constraints involve the individual characteristics of the learner (organismic constraints), the requirements of the task (task constraints), and the environmental conditions (environmental constraints).…”
Section: Introductionmentioning
confidence: 99%